Environmental drivers affecting the status of top commercial fish stocks in the Baltic Sea: review - Rosciszewski-Dodgson, Michael J.; Cirella, Giuseppe T. (Frontiers in Marine Science, 2024)
Introduction Like in many parts of the world, the Baltic Sea experiences a multitude of processes and stressors that influence fish stock dynamics. This paper compartmentalizes 250 publications that examine the cumulative effects and trade-offs of some of the most significant environmental drivers (temperature change, hypoxia, nutrient enrichment, acidification, low salinity, and food-web dynamics) on the ecology of top commercial fish species in the Baltic Sea (cod, sprat, whiting, herring, flounder, and plaice). Methods A systematic review method was applied to ensure rigorous coverage of existing literature and to provide a comprehensive synthesis of the current knowledge on the subject. Results The results illustrate the extent of scientific research applicable to commercial fisheries knowledge in the Baltic Sea and identify which pressures have the greatest negative impacts on which stocks. Additionally, the findings demonstrate how well top commercial fish species have adapted to the changing environmental conditions of the Baltic Sea. In doing so, the review illustrates the upcoming challenges and underscores which stocks are likely to dominate in the future and which will face difficulties. Discussion By considering ecosystem-based fisheries management, this paper emphasizes the need to account for complex ecosystem interactions beyond single-stock monitoring. With increased natural hazards, top commercial fish species have reacted differently, depending on the region and their adaptive capabilities. In most cases, Clupeidae species have adapted the best to their new surroundings, Pleuronectidae resilience is varied, while Gadidae species are finding the Baltic Sea increasingly challenging.